Influence of Soil Moisture Regimes, Amendments and Ageing on Nickel Availability in Soils - and Dhanwinder Singh, Shehnaz*, R. Sikka (Journal of the Indian Society of Soil Science, 2021)
In a range of nickel (Ni) spiked soils the effects of soil moisture regimes, amendments and ageing on Ni availability were estimated. The soil was spiked with Ni @ 0, 10 and 25 mg kg-1 soil through its nitrate solution. Lime (5%), farmyard manure (20 t FYM ha-1) and zinc (25 mg Zn kg-1) were added. The treated soil samples were incubated at 35 Â°C for 1, 45 and 90 days at field capacity and submerged soil moisture regimes. Available Ni was extracted with 0.005 M DTPA extractant and determined by ICP-AES. The results revealed that there was a temporal decrease in the available Ni with ageing and was in the order of 1 day > 45 days > 90 days. The magnitude of decrease in Ni availability was higher with the addition of amendments in the order of lime > FYM > Zn > unamended soil. The decrease in available Ni was further pronounced under submerged moisture regime than under field capacity. The mean per cent recovery of DTPA-Ni in the 10 mg Ni kg-1 spiked treatment decreased from 57.6 after 1 day of incubation to 29.3 and 26.8 after 45 and 90 days of incubation, respectively; whereas in the 25 mg Ni kg-1 spiked soil, per cent recovery of Ni decreased from 60.0 after 1 day of incubation to 29.0 and 25.1 after 45 and 90 days of incubation, respectively. An overall reduction in the mean per cent recovery of DTPA-Ni was observed under submergence as compared to field capacity moisture regime in lime, FYM, Zn amended soils and unamended soil. The results enable us to understand the effect of ageing coupled with different amendments under various moisture regimes on Ni availability and provide useful information to work out the capacity of the soil to serve as a sink for Ni.